2022
DOI: 10.1002/inf2.12395
|View full text |Cite
|
Sign up to set email alerts
|

Back Cover Image

Abstract: This cover (DOI: 10.1002/inf2.12345) shows a multifunctional TPA‐azaBODIPY‐TPA small molecule with superior optoelectronic and photophysical properties. Material is shown to function as an efficient hole transport layer in perovskite solar cells reaching a power conversion efficiency of 17.4%, and as a robust electron donor in near‐infrared organic photodetectors absorbing light in the wavelength range of up to 800 nm. Offering two distinct optoelectronic functions, TPA‐azaBODIPY‐TPA is particularly attractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In general, adjusting the blend ratio alters the blend morphology and affects the performance of organic optoelectronic devices. [ 22 ] Here, we used atomic force microscopy (AFM) and grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) to examine the blend morphologies. Figure a displays topographical and phase images of the 1:1 and 1:1.2 (250 nm) blend films.…”
Section: Resultsmentioning
confidence: 99%
“…In general, adjusting the blend ratio alters the blend morphology and affects the performance of organic optoelectronic devices. [ 22 ] Here, we used atomic force microscopy (AFM) and grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) to examine the blend morphologies. Figure a displays topographical and phase images of the 1:1 and 1:1.2 (250 nm) blend films.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, it is the simplest of the NIR-AZA uorophore class, which is more commonly further derivatised to suit a diverse set of biological and material purposes. [8][9][10][11][12][13][14][15][16][17] Previously we have shown that 1 and P 188 spontaneously undergo a DSA in water to form nanoparticles NP1-P 188 of ∼100 nm size with the uorescence from 1 quenched (Fig. 1C).…”
Section: Introductionmentioning
confidence: 87%
“…Structurally, it is the simplest of the NIR-AZA fluorophore class, which is more commonly further derivatised to suit a diverse set of biological and material purposes. 8–17…”
Section: Introductionmentioning
confidence: 99%
“…[ 2–5 ] The unique optoelectronic properties of π‐conjugated organic semiconductors have found countless applications, including image sensing, [ 6–8 ] colour discrimination, [ 7,8 ] optical communication, [ 7,9 ] X‐Ray detection, [ 10,11 ] electronic skin (e‐skin), [ 7,12 ] medical implants, [ 13,14 ] brain sensors [ 15–17 ] and health monitoring. [ 18–20 ] Near‐infrared (NIR) OPDs, [ 21,22 ] that offer additional advantages of reduced light scattering, minimal absorption and high tissue penetration, [ 23–25 ] have been of capital importance in optical, biomedical and photoacoustic imaging, [ 23,26–28 ] as well for food quality inspection, [ 29 ] artificial vision, [ 30,31 ] night vision [ 32 ] and military surveillance. [ 33 ] While much progress has been demonstrated in recent years, [ 24,34 ] NIR OPDs remain challenging to manufacture, especially in the short‐wave infrared region (SWIR, 1–3 µm).…”
Section: Introductionmentioning
confidence: 99%